-8x+6(x+4)=6

Simple and best practice solution for -8x+6(x+4)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+6(x+4)=6 equation:



-8x+6(x+4)=6
We move all terms to the left:
-8x+6(x+4)-(6)=0
We multiply parentheses
-8x+6x+24-6=0
We add all the numbers together, and all the variables
-2x+18=0
We move all terms containing x to the left, all other terms to the right
-2x=-18
x=-18/-2
x=+9

See similar equations:

| -8g-6=-7g | | 8-7d=1-9d-5 | | 19(40-x)+69=20+55 | | -10+6p=10+4p | | 1/2a=14 | | -16n+8=-15n-8 | | X+(2X-100)=180-y | | x/15.8=9.2/23.6 | | 7x^2+180x-900=0 | | (15b-4)-7(2b+1)=-6 | | s/6+14=45 | | (15b-4)-7(2b+`)=-6 | | -999(n^2+1)=2000n | | 5^2x-1=125^3x+2 | | 4x²-360=0 | | V=10-v | | 15x-12+6x=180 | | 8-5c=-9-9c-7 | | -x+5=-4x+14 | | 1/3(6y-9)=5 | | 4r-5=7+r | | 3-9u=7-8u | | 1.25=x+x^2 | | -15h-15+17h=-2h+17 | | (5x+2)(x-3)=12 | | x=7.248x0.19 | | 1/2(6x+4)=5(2-8) | | 33-18=3(x-9) | | 9n^2–25=0 | | .04x+.07(100-x)=5 | | 21m+86=m+5 | | 114+(2y)=90 |

Equations solver categories